Hypnobirthing untuk Mengurangi Kecemasan pada Ibu Hamil Trimester III - Wahyu Indah Lestari; Hapsari Windayanti; Nafa Nofitasari; Ana Zully Astuti; Alya Fernanda Khairani (Universitas Ngudi Waluyo, 2022)
Pregnancy is a meeting between sperm and ovum so that nidation occurs. In pregnancy there are 2 changes, namely physiological changes and psychological changes. These changes are caused by maternal adaptation which is the result of the work of pregnancy hormones and the mechanical pressure of the uterus which continues to enlarge and the presence of tissues that contribute differently. This adaptation is also divided into 2, namely physiological and psychological adaptations. In the first trimester there is nausea and vomiting and significant mood swings. For the second trimester is characterized by an improved appetite and begins to realize about the feelings experienced. In the third trimester there is excessive anxiety which causes fear during labor. For this reason, management is needed in the face of labor. This management can be in the form of complementary therapies, namely hypnotherapy, yoga, and acupressure. The most appropriate therapy to deal with anxiety is hypnotherapy or commonly called hypnobirthing. Hypnobirthing is relaxation with the addition of suggestions through strokes. The hand becomes a means to rub the area under the breast to the stomach. Even this method has been done by pregnant women when the baby struggles in the womb. This study aims to analyze the effect of hypnobirthing techniques on reducing anxiety levels in third trimester pregnant women in facing childbirth. The method used in writing this journal uses a literature review study, which is a search for literature both internationally and nationally. Sources for conducting this literature review include a systematic search study of computerized databases using Google Scholar, Pubmed, and Proquest. At the journal search stage using the keywords